Salinity limits mosquitofish invasiveness by altering female activity during mate choice - Pirroni, Sara; Leggieri, Francesca; Cuccuru, Jessica; Domenici, Paolo; Brown, Mark J. F.; Marras, Stefano; Riesch, Rüdiger (Frontiers in Fish Science, 2024)
Biological invasions of freshwater habitats are of increasing biological and economical concern, and both, salinity and parasites are considered to be key contributors to invasion success. Salinity, for example, influences the distribution of invasive mosquitofish (Gambusia holbrooki) and native killifish (Aphanius fasciatus) in Europe, with the latter now predominantly confined to high-salinity habitats. Here, we examined how salinity might affect female activity and preference for large and non-parasitized males in multiple populations of mosquitofish and killifish in Sardinia, Italy. We predicted that (1) females of both species would associate preferentially with larger and uninfected males, and that (2) female behaviour in both species would be significantly influenced by salinity. We used dichotomous choice tests, in which we presented focal females with video animations of photos of the same male but differing in body size and presence/absence of an ectoparasite (Lernaea cyprinacea). We calculated female preference based on association time and quantified female inactivity as time spent in the central neutral zone during trials. Contrary to prediction 1, females did not prefer the large or uninfected male stimuli over their counterparts in any of the populations. However, while salinity did not significantly affect female preferences, it did significantly affect their activity, with mosquitofish becoming more inactive at higher salinities and killifish exhibiting the opposite pattern, matching prediction 2. These results suggest that salinity limits mosquitofish invasiveness by reducing their activity and thus provides a refuge for the Mediterranean killifish.